2019
DOI: 10.1155/2019/9030563
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Cell Death and Cardiovascular Diseases

Abstract: ROS functions as a second messenger and modulates multiple signaling pathways under the physiological conditions. However, excessive intracellular ROS causes damage to the molecular components of the cell, which promotes the pathogenesis of various human diseases. Cardiovascular diseases are serious threats to human health with extremely high rates of morbidity and mortality. Dysregulation of cell death promotes the pathogenesis of cardiovascular diseases and is the clinical target during the disease treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 112 publications
1
64
0
1
Order By: Relevance
“…Due to the fact that serotonin metabolism disorder is one of the pathogens in panic, the results of the present study are confirmed. In other words, increased serotonin levels elevate its catabolism and as a result the activity of the enzyme monoamine oxidase, which in turn leads to the induction and increase of oxidative stress (Hamzekolaei et al, 2020; Sturza, et al, 2019; Sturza, et al, 2019; Xu et al, 2019), demonstrated in our results by reduced level of glutathione and glutathione peroxidase activists and elevated levels of carbonyl proteins. Our previous study also reported an increase in malondialdehyde levels as an indicator of oxidative stress (Hamzekolaei et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…Due to the fact that serotonin metabolism disorder is one of the pathogens in panic, the results of the present study are confirmed. In other words, increased serotonin levels elevate its catabolism and as a result the activity of the enzyme monoamine oxidase, which in turn leads to the induction and increase of oxidative stress (Hamzekolaei et al, 2020; Sturza, et al, 2019; Sturza, et al, 2019; Xu et al, 2019), demonstrated in our results by reduced level of glutathione and glutathione peroxidase activists and elevated levels of carbonyl proteins. Our previous study also reported an increase in malondialdehyde levels as an indicator of oxidative stress (Hamzekolaei et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…Oxidative stress, which is defined as excessive production of reactive oxygen species (ROS) and disproportion of oxidants over antioxidants, causes myocardial remodeling by activating hypertrophy-signaling kinases and stimulating cardiac fibroblasts to proliferate. ROS also affect myocardial calcium handling and lead to cellular dysfunction by inducing changes in intracellular pathways [59,60]. Moreover, in dysfunctional myocardium, enhanced ROS production is observed, and the antioxidant mechanism's exhaustion leads to disease progression [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to the formation of proteotoxic soluble peptides [ 70 ]. The cardioprotective effect of HSPs is manifested in an increased cell resistance to hypoxia [ 71 ] and oxidative stress [ 72 ] and in increase in functional recovery with a decreased infarction size after experimental induction of I/R [ 73 , 74 ]. The restoration of blood flow after ischemia leads to massive production of ROS, which generate severe damage to biomolecules—a phenomenon called myocardial reperfusion injury [ 10 ].…”
Section: Heat Shock Proteins In Ischemia/reperfusion Injurymentioning
confidence: 99%